Evaluasi Sistem Instalasi Tenaga Listrik berdasarkan Standar PUIL 2011 (Studi Kasus Pada PT. Multi Nabati Sulawesi Luwuk) - Anggi; Jumiati Ilham; Amirudin Yunus Dako (Transbahasa, 2025)
Electrical power installation systems in the industrial sector require proper planning in accordance with the General Electrical Installation Requirements (PUIL 2011). Common issues in industrial electrical installation systems include voltage drop on the load side, unbalanced loads, and low power factor during power distribution and utilization. Therefore, this study aims to evaluate the electrical power installation system at PT. Multi Nabati Sulawesi-Luwuk to ensure it operates effectively and efficiently while addressing potential disturbances. The research employs an evaluation method consisting of literature study, data collection through observation and interviews, and analysis of installation compliance based on the PUIL 2011 standard. The results indicate that most electrical installation components, including conductor ampacity (KHA), circuit breakers, transformer loading, transformer load balance, and transformer loading percentage, comply with the PUIL 2011 standards. However, for the motor carrier’s KHA, the conductor used is smaller than the standard requirement, making it non-compliant. This evaluation is expected to serve as a reference for improving the quality of electrical installations at PT. Multi Nabati Sulawesi-Luwuk.